Relevance of mandatory glaucoma screening in all patients from outreach cataract camps referred to a base hospital for cataract surgery - Tomar, Vijay P. S.; Sharma, Sandeep; Bhardwaj, Rahul; Bamel, Arjun; Bobade, Amrapali; Bhadauria, Madhu (International Journal Of Community Medicine And Public Health, 2020)
Background: Glaucoma is the first cause of irreversible blindness and second leading cause of visual loss in the world. The purpose of this study was to conduct mandatory glaucoma screening and to find out the prevalence of glaucoma, in all patients referred for cataract surgery to a base hospital. Methods: A retrospective analysis was conducted of all patients referred from rural screening camps to base hospital for cataract surgery. Medical records of 5024 consecutive patients referred to base hospital from the month of January to June 2019 were reviewed. All these 5024 patients underwent comprehensive ophthalmic and systemic examination. Those patients in which glaucoma was suspected, were referred to glaucoma clinic for further evaluation. Results: Total 5024 patient’s records were analysed retrospectively. The mean age of the participants was 57.2±8.149 ranged from 40-95 years and average age of patients having cataract with glaucoma was 61.3±9.423. Total patients of glaucoma with cataract were 188 (3.7%). The prevalence of primary open angle glaucoma (POAG) and Primary angle closure glaucoma (PACG) was 1.69% and 1.17% respectively while secondary glaucoma was found in 0.88% of the patients. The prevalence of ocular hypertension, PAC and PACS was 0.33%, 0.29% and 0.83% respectively. Conclusion: The prevalence of glaucoma in this study was 3.7% of those planned for cataract surgery. Therefore, mandatory glaucoma screening in all patients from outreach cataract camps would result in detection of a large number of those with undiagnosed glaucoma.